Transformation of the educational process: managing the integration of digital technologies and modern educational strategies - Natalya I. Golovanova; Evgenia A. Smirnova (RUDN Journal of Public Administration, 2025)
In the context of the rapid development of digital technologies and their active integration into educational processes, managing digital transformation has become one of the most critical tasks for the modern educational system. Changes brought about by digitalization require the reevaluation of established teaching approaches, the adoption of innovative instructional methods, and the effective management of digital tools’ integration. This study addresses issues related to the development and implementation of management mechanisms aimed at the successful incorporation of digital technologies and modern educational strategies into the learning process. Special attention is given to analyzing key approaches that facilitate educational institutions’ adaptation to the challenges of the digital era. The study explores examples of advanced technologies, such as virtual and augmented reality, interactive educational platforms, project-based learning, and other tools that help develop critical thinking, creativity, digital literacy, and teamwork skills in students. These approaches not only enrich the learning process but also make it more adaptable and effective. The importance of state and municipal support is emphasized, particularly in creating favorable conditions for integrating innovations, including developing infrastructure, enhancing teacher qualifications, and providing resources for implementing digital solutions. The study also highlights the need for continuous monitoring of the outcomes of digital technologies and educational strategies to ensure their ongoing optimization. This study focuses on identifying factors that influence the effectiveness of managing educational transformation processes and formulates recommendations for improving the efficiency of educational institutions. The study contributes to the development of theories and practices in educational system management within the context of digital transformation, offering tools and approaches that will be valuable to researchers, educators, and educational administrators.